IDENTIFIKASI PERILAKU SEKS BEBAS AKIBAT KONSUMSI MINUMAN BERALKOHOL PADA PENGUNJUNG REMAJA KELAB MALAM â€œXâ€ SEMARANG - Putra, Ardhianto Pradhana; Cahyo, Kusyogo; Widagdo, Laksmono (Jurnal Kesehatan Masyarakat (e-Journal), 2018)
At 2010 Indonesian consumption alcohol rate was 7.1 liter per year. Quoting from BKKBN at 2014 half of the urban girl dan 62,7% junior high school girl has give away their virginity. Quoting from the Journal of Addiction the alcohol consumption at spesific rate can lead to a risky sex. The purpose of this study is to identify free sex behavior due to alcohol consumption in nightclub visitors "X" Semarang. TThe qualitative method is used with descriptive approach and the technique for collecting data is in-depth interview. The main research subjects in this study were teenage visitors of nightclub age 17-24 years who have not married and had sex due to the influence of alcohol in the last year. Validating data using source triangulation with subject triangulation of "X" nightclub manager, "X" nightclub manager and a friend of the main research subjects. The result of this research is the identification of factors that influence to the adolescent of nightclub â€œXâ€ Semarang in free sex behavior due to alcohol consumption that is the level of adolescent education, youth income, adolescent knowledge about free sex and its impact, attitude toward consuming teenage alcohol, environment adolescent friendship, adolescent family circumstances, teenage boyfriends, affordability of alcoholic beverage prices by adolescents, availability of places to have free sex in Semarang City, and availability of health information at nightclub â€œXâ€ Semarang. While the factors that do not support the youth nightclub adolescents in free sex behavior due to alcohol consumption are adolescent knowledge about alcohol and its effects, and adolescent attitudes toward free sex and its effects. Thus free sex under the influence of alcohol to a sufficient level in the blood makes the subject's sex behavior riskier review of the stage of sexual behavior and proved the impact felt by the research subject of unwanted pregnancies and vaginal discharge.